(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Saleh AR, Gusli S, Ala A, Neswati R, Sudewi S. 2021. Tree density impact on growth, roots length density, and yield in agroforestry based cocoa. Biodiversitas 23: 496-506. Cocoa-based agroforestry systems using langsat trees as shade is aimed to maximize the absorptions of solar energy, water, and nutrients, and increase income sources for farmers. Limited information about interspecific interactions between cocoa and langsat which is needed to improve the performance of agroforestry systems is a challenging idea. We studied the relationship characteristics of cocoa trees as a present shaded effect in the agroforestry system. Compared agroforestry systems were based on ages, namely young and old cocoa agroforestry or YCAF and OCAF, and monoculture systems (Mono) regardless of plant age. On above stony soil, we observed root length density (RLD) of cocoa and langsat fine roots, from under cocoa canopy to three distance levels from the cocoa stem (i.e. at a distance 0.4 m, 1.2 m and, 1.7 m), and four distance depths for all systems (i.e. at a depth 0-10 cm, 10-20 cm, 20-30 cm and, 30-40 cm). Stem diameter, basal area, canopy cover, yield cocoa beans, and convertible products non-cocoa were equivalent to the price of cocoa beans by tree equivalent yield (TEY) formula. Cocoa RLD in the Mono system did not differ from RLD-cocoa in the OCAF system, but both significantly differed with RLD-cocoa in the YCAF system. Shade trees increased tree density in both agroforestry systems, triggering competition in the canopy for sunlight. Expansion of langsat roots that spread closer to the cocoa trunk increased competition for nutrients and water. Both cocoa and langsat roots overlapped, exploring the same area. The yield of cocoa beans harvested by farmers from the YCAF and OCAF systems decreased by 50%. However, the langsat tree and several other species were accounted for 50% of the TEY in the agroforestry system, thereby adding a source of income to farmers is equivalent to the yield of cocoa beans from a monoculture system.